A Rite of Transformation in harmonia oppositorum: “Habitación en Roma” by Jorge Eduardo Eielson - Cavagnaro Farfán, Franco (2023)
The enunciated principle of two complementary elements from two different civilizations (harmonia oppositorum / yanantin) converges in Eielson’s poetic and plastic work to create. In his work, the city of Rome serves as a platform center that enables him to rediscover cosmological ways of seeing that connect different levels. For this article, we use Habitación en Roma, his articles from the 1950s, as well as statements made in the 1970s, 1980s, and in the 21st century. From the vestige, the creation of objects is replicated in his poetic and visual work and in his procedures with matter. Through this, it is possible to transform and be transformed after reaching moments of ultra-consciousness.